2020 IEEE Latin-American Test Symposium (LATS) 2020
DOI: 10.1109/lats49555.2020.9093670
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Code Encryption Effects on Memory Fault Resilience

Abstract: In most safety-critical systems, the robustness and the confidentiality of the application code are crucial. Such code is generally stored into Non-Volatile Memories (NVMs) that are prone to faults (e.g., due to radiation effects). Unfortunately, faults affecting the instruction code result very often into Silent Data Corruption (SDC). This condition lets faults remain undetected and it can lead to undesiderable errors that may compromise the system functionality. Thus, it is desirable that the system is able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
1
3
1
Order By: Relevance
“…Specifically, for fault multiplicity higher than 200 the block ciphers' detection rates drop. These results show a contrasting trend compared to our previous work [6], where we found that the block ciphers have a high detection capability for faults occurring in the code memory space (see Section II). Indeed, a fault may transform an instruction into an illegal one, causing a failure in the code execution.…”
Section: A No Pad: Experiments Without Padding Checkscontrasting
confidence: 96%
See 3 more Smart Citations
“…Specifically, for fault multiplicity higher than 200 the block ciphers' detection rates drop. These results show a contrasting trend compared to our previous work [6], where we found that the block ciphers have a high detection capability for faults occurring in the code memory space (see Section II). Indeed, a fault may transform an instruction into an illegal one, causing a failure in the code execution.…”
Section: A No Pad: Experiments Without Padding Checkscontrasting
confidence: 96%
“…Block ciphers perform better than the stream ciphers. In this scenario, we obtained a trend similar to the one observed in our previous study [6]. Finally, regardless of the multiplicity of the injected faults, the PCBC configuration achieves ≈ 100% detection rate.…”
Section: B Pad: Experiments With Padding Checkssupporting
confidence: 86%
See 2 more Smart Citations
“…We perform fault injection campaigns only on the ML application weights and not on other ML data or application code. Concerning the application code, in a previous work [40] we have shown that encryption enables high fault detection rates. We classify faults as follows:…”
Section: A Fault Models Fault Classification and Fault Effectsmentioning
confidence: 97%